The Effect of Leadership Style on Performance in Shariah Ranihah Abadi Makmur Cooperation - Zaidun Zaidun (eCo-Fin, 2019)
This study aims to determine the magnitude of the influence of leadership style on the performance of employees in the Syariah Financing Cooperative Savings and Loans (KSPPS) Rabihah Abadi Makmurm Belitang III east OKU. The conclusion obtained is r = 0.772 which has been consulted with a conservative standard which is located between 0.60-0.799 which means it is classified as a strong correlation or influence between leadership style and employee performance in Sharia Financing Savings and Credit Cooperatives (KSPPS) Rabihah Abadi Makmur Belitang III East OKU and after hypothesis testing known t count = 3.66 and t table obtained 1.833. The advice that can be given is that the cooperative must provide training to employees so that they understand more deeplycarry out their duties so that employees can improve their performance